HUBUNGAN POLA ASUH IBU DENGAN REGULASI DIRI REMAJA AKHIR - Natasya Hanan Putri; Weny Savitry S. Pandia; Desy Chrisnatalia (Faculty of Psychology, Atma Jaya Catholic University of Indonesia, 2020)
Late adolescent aged 18-25 are expected to overcome obstacles and make decisions as transition to adulthood. Self-regulation is needed that adolescents had to have self-control. Self-regulation is an individual's ability to consider goals, commitments and rewards to respond environmental demands. Maternal parenting style is an important thing to form selfregulation. Maternal parenting style is mother’s set rules, reward, punishmet and respond to children’s behavior. This quantitative study aims to describe the relationship between maternal parenting style and late adolescent’sself-regulation. The participants were 134 teenagers aged 18 to 25 living with their mother. The instruments are Self-Regulation Questionnaire and Scale of Parenting Style. The data was analysed using Pearson correlation techniques. The results showed significant correlation between maternal parenting style and late adolescent’s selfregulation (r = .348, p<.01, two tailed). This result fitted with previous research which stated that primary environment is considered to have great role in late adolescent’s self-regulation than other factors.